The Relationship between Age and Parity in Pregnancy to the Incidence of Anemia in the Working Area of the Sipatana Health Center - Ardha Nurul Ahmad; Sri Mulyaningsih; Levana Sondakh; Rizky Nikmathul Husna Ali (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2025)
Anemia in pregnant women has serious implications for both mother and baby, including fatigue, heart complications, infections, hemorrhage during delivery, postpartum depression, and even death. For the baby, anemia can lead to prematurity, growth and developmental delays, low birth weight, and mortality. The highest incidence of anemia occurs in women aged under 20 and over 35 years and is more common in women with high parity due to increased plasma volume and hemodilution. Management of anemia in pregnancy can be achieved through health education, antenatal care (ANC) examinations, and regular consumption of iron (Fe) tablets. This study aims to determine the relationship between maternal age and parity and the incidence of anemia in the working area of Sipatana Public Health Center. This research used an analytic method with a cross-sectional design and involved 104 pregnant women as respondents. The results showed that pregnant women in the at-risk age group had a 0.140 times lower likelihood of experiencing anemia based on statistical tests (p = 0.034). Meanwhile, women with high parity had a 3.628 times greater risk of experiencing anemia (p = 0.033). Conclusion: There is a significant relationship between maternal age and parity and the incidence of anemia in the working area of Sipatana Public Health Center.